Pemanfaatan Our Moderate Game Berbasis Game Based Learning Guna Membangun Sikap Toleransi Beragama Siswa Man 2 Banyumas - Adhitya Ridwan Budhi Prasetyo Nugroho; Muhammad Yusuf Ramadhan (Madaris: Jurnal Guru Inovatif, 2024)
In the context of Indonesian society, which is diverse in terms of religion, tradition, culture becomes a very vulnerable condition for socio-religious conflicts, one of which is intolerance in adolescents. Game based learning offers interactions that allow them to explore socio-religious roles, test new ideas, and develop skills through play. This research uses a mix method. Data collection was carried out using questionnaires, observations and interviews were conducted in Banyumas Regency to test the effectiveness of the game . The results in this study are Our Moderate Game (OMG) is a game that provides religious tolerance education with a virtual journey model in various regions in Indonesia. The results in this study namelyOur Moderate Game (OMG) is a game that provides education on religious tolerance with a virtual journey model in various regions in Indonesia.Our Moderate Game (OMG) Effective in increasing the Religious Tolerance of Banyumas MAN 2 students with an average score of religious tolerance in the control class of 66.10, while in the experimental class, the average score of Religious Tolerance was 80.53. Based on gender, male students had a higher level of religious tolerance, namely 82.71, compared to female students, namely 81.56.